2014
DOI: 10.1016/j.medici.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial usage among hospitalized children in Latvia: A neonatal and pediatric antimicrobial point prevalence survey

Abstract: We identified a few problematic areas, which need improvement: the high use of third-generation cephalosporins for pediatric patients, prolonged surgical prophylaxis, predominant use of parenteral antibiotics and an urgent need for local antibiotic guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
6
8
4
1
Order By: Relevance
“…In the global Antibiotic Resistance and Prescribing in European Children (ARPEC) PPS study conducted in 2012, involving 226 hospitals from 41 countries, the overall percentage of hospitalized children on antimicrobials was 42.5%, which was much lower than the 61.5% in our study [ 8 ]. The percentage of patients on antimicrobials in our study was higher than reported in Turkey (54.6%) [ 9 ], Italy (47%) [ 10 ], Australia (46%) [ 11 ], the United Kingdom (40.9%) [ 12 ], Latvia (39%) [ 13 ], and the United States (33%) [ 14 ]. However, it was lower than in Iran (66.6%) [ 15 ] and China (78.2%) [ 16 ].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In the global Antibiotic Resistance and Prescribing in European Children (ARPEC) PPS study conducted in 2012, involving 226 hospitals from 41 countries, the overall percentage of hospitalized children on antimicrobials was 42.5%, which was much lower than the 61.5% in our study [ 8 ]. The percentage of patients on antimicrobials in our study was higher than reported in Turkey (54.6%) [ 9 ], Italy (47%) [ 10 ], Australia (46%) [ 11 ], the United Kingdom (40.9%) [ 12 ], Latvia (39%) [ 13 ], and the United States (33%) [ 14 ]. However, it was lower than in Iran (66.6%) [ 15 ] and China (78.2%) [ 16 ].…”
Section: Discussioncontrasting
confidence: 72%
“…LRTI was the most common indication for prescribing antimicrobials, a finding consistent with PPSs among hospitalized children in several other countries [ 10 , 11 , 12 , 13 ]. Third-generation cephalosporins were the most commonly prescribed antibiotics for LRTI in this study.…”
Section: Discussionsupporting
confidence: 65%
“…Still the figure for injections appears to be high and calls for investigation through prescription audit and formulation of antibiotic guidelines. Comparative concerns have been voiced in a recent latvian investigation on antibiotic usage among hospitalized children, including neonates [24]. The near 100% generic prescribing is a desirable situation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar concerns have been voiced in a recent Latvian study on antimicrobial usage among hospitalized children, including neonates. [21] The near 100% generic prescribing is a desirable situation. We feel that this owes to a large extent on local government policy that seeks to enforce generic prescribing in public hospitals.…”
Section: Discussionmentioning
confidence: 99%